EFFECTIVENESS OF “BERHITUNG CEPAT” TRAINING ON THE FOUNDATIONAL MATHEMATICS COMPETENCE OF MADRASAH IBTIDAIYAH TEACHER’S - Andi Susanto; Fitria Mardika; Ibnul Anies (UIN Imam Bonjol Padang, 2026)
This study investigates how effective rapid calculation training is in improving the basic math skills of Madrasah Ibtidaiyah (MI) teachers in West Sumatra. This research was conducted because teachers rarely use effective calculation strategies and there are no professional development programs specifically aimed at enhancing their basic math skills. A quantitative method was used with a single pretest-posttest group. The study involved 125 teachers from four Madrasah Ibtidaiyah located in West Sumatra, and 96 participants were selected using purposive sampling. Data were collected through rapid calculation tests administered before and after the training intervention. Paired-sample t-tests and the N-Gain index were used to analyze the collected data. The results showed a statistically significant improvement in participants' performance after the training, with a significance value of 0.000 (p < 0.05). In the posttest, the average score increased from 36.00 in the pretest to 67.27 in the posttest. In addition, the level of participant competence improvement is shown by an N-Gain value of 0.49. The results indicate that calculation training is effective in quickly improving the basic mathematics competence of MI teachers. These results also show that this type of training can serve as a feasible professional development program to enhance teachers' mathematics skills and improve the quality of mathematics learning in Madrasah Ibtidaiyah.